Exudates Detection in Fundus Images - Kalita, Abhinandan (International Journal of Computer Sciences and Engineering, 2019)
Diabetic retinopathy is the main cause of vision loss in diabetic patients. It is caused by the damage of retinal blood vessels due to prolonged diabetes. This paper investigates on some image processing operations to extract exudates for the analysis of diabetic retinopathy. The proposed method stands out prominent in terms of specificity and accuracy.